Critical Theory and Political Modernity - Domingues, José Maurício; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
"This book represents a significant and original contribution to the field. It displays an enormous depth of knowledge in its distinctive account of political modernity-its problems and potentials. It is one of the more stereoscopic works recently produced in the broad field of critical theory." -Craig Browne, Senior Lecturer in Sociology, The University of Sydney, Australia This work of political sociology draws together philosophy, jurisprudence, political science, and international relations to study the main categories of political modernity and its development trends. Grounded in critical theory-from Marx to later currents such as the Frankfurt School-Critical Theory and Political Modernity circulates around state power and oligarchy as well as emancipatory possibilities from their foundations to the present, such as radical democracy. Domingues analyzes the main categories of political modernity, including the juridical dimension, to conceptually articulateits long-term processes of development. In so doing, he examines rights, law and citizenship, state and domination abstract and concrete, the political system, state power, freedom and autonomy, scalar configurations, political regimes, oligarchy and democracy.
Introduction -- Part I -- Chapter 1: The Dual Individual and Its Rights -- Chapter 2: The State as Abstraction -- Chapter 3: From Abstract to Concrete -- Part II -- Chapter 4: The Political System -- Chapter 5: State Power, Autonomy, and Developmental Trends -- Chapter 6: The Developmental Dynamics of Citizenship and Autonomy -- Chapter 7: Global Ramifications: Sovereignty and Autonomy -- Part III -- Chapter 8: Regimes. - Chapter 9: Radical Democracy.
Keywords: Sociology; Social structure; Equality; Political sociology; Political science; Sociological Theory; Social Structure; Political Sociology; Political Theory